Lionfish Diet Composition at Three Study Sites in the Aegean Sea: An Invasive Generalist? - Ioannis E. Batjakas; Athanasios Evangelopoulos; Maria Giannou; Sofia Pappou; Eleftheria Papanikola; Maria Atsikvasi; Dimitris Poursanidis; Chrysoula Gubili (Fishes, 2023)
The diet of the lionfish (Pterois miles), an invasive species in the Aegean Sea, was examined by collecting stomach content data from fish collected in three study sites in the Aegean Sea (southern Crete, Kastellorizo, and Nysiros islands). Prey composition in terms of numerical abundance and frequency of occurrence was used to compare lionfish’s diet between these sites. Lionfish largely preyed upon teleosts (4% to 83% numerical abundance and 16% to 58% frequency of occurrence, depending on the site) and decapods (12% to 95% numerical abundance and 11% to 81% frequency of occurrence). The most important teleost families in lionfish’s diet were Gobiidae, Labridae, and Scorpaenidae, while decapods and especially the family Scyllaridae and the genus Plesionika were the dominant decapod prey items. The lionfish was found to be an especially successful generalist across the study sites, an opportunistic, predatory species overall, and at the same time, at a local level, it seems to be an equally successful specialist that could increase the predation mortality of already stressed prey populations and can be a serious threat to endemic, critically endangered, and/or commercially important species.